Supervisi Berjenjang di Era Pandemi COVID-19 dalam Manajemen Keperawatan - Eva Yuliana; Rr. Tutik Sri Hariyati; Rusdiansyah Rusdiansyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to analyze tiered supervision in the nursing service area during the COVID-19 pandemic. The research method uses a case study approach with interviews, document review and observation, and performs problem analysis using fishbone analysis. The results showed that the tiered supervision function was less than optimal in the COVID-19 pandemic conditions at Hospital X so that it had an impact on the quality of nursing care. Nursing managers from the top manager to the first manager at RS X only supervise verbally, without a routine schedule, without supervision tools and no tiered supervision standards and have not developed follow-up steps on supervision results in each nursing service area. In conclusion, the optimization of tiered supervision in the pandemic era can be carried out through the innovation of the tiered supervision method with the G-Spreadsheet digital application, which is carried out by all levels of nursing managers at X Hospital. Keywords: Nursing Management, Roles and Functions of Nursing Managers, Nursing Supervision